Successful perinatal management in pregnant women with R9 limb-girdle muscular dystrophy and left ventricular ejection fraction of 27%: a case report - Xie, Wenchi; Huang, Lok Chong; Luo, Dan; Kang, Landan; Hu, Koubihan; Liu, Xiong; Mei, Jie (Frontiers in Medicine, 2025)
A 29-year-old woman with muscle weakness at 26 + 5 weeks of pregnancy was hospitalized for heart failure, and genetic testing revealed that she had R9 limb-girdle muscular dystrophy (LGMDR9). Since LGMDR9 is associated with cardiac and respiratory dysfunction, we promoted fetal lung maturation and performed an emergency cesarean section at 29 + 2 weeks to prevent further deterioration of cardiac function and muscle weakness. This case highlights the importance of choosing the right mode of delivery, timing of delivery, and early genetic testing for LGMDR9 patients.